223k views
3 votes
What is the solution to this equation?
6(x-3) = 3х+9 ​

What is the solution to this equation? 6(x-3) = 3х+9 ​-example-1
User Mahesh
by
4.7k points

2 Answers

2 votes

Answer:

B.) x = 9

Explanation:

6(x - 3) = 3х + 9

6x - 18 = 3x + 9

6x - 3x = 18 + 9

3x = 27

x = 27/3

x = 9

User Jaxon
by
4.9k points
0 votes

Answer:

x = 9

Explanation:

6(x-3) = 3x+9

Distribute

6x-18 = 3x+9

Subtract 3x from each side

6x-3x -18 = 3x-3x+9

3x -18 = 9

Add 18 to each side

3x-18+18 = 9+18

3x = 27

Divide each side by 3

3x/3 = 27/3

x = 9

User Ahmed Moheb
by
4.5k points